“Cattle Welfare Is Basically Human Welfare”: Workers' Perceptions of ‘Animal Welfare' on Two Dairies in China - Chen, Maria; Weary, Daniel M. (Frontiers in Veterinary Science, 2022)
‘Animal welfare’ (动物福利) is a foreign term in China, and stakeholder interpretations can affect receptiveness to the concept. Our aim was to explore workers’ perceptions of animal welfare on two dairies in China. We used a mini-ethnographic case study design, with the first author (MC) living for 38 days on one farm and 23 days on a second farm. MC conducted semi-structured interviews (n=13) and participant observations (n=41) with farm management and staff. We used template analysis to generate key themes from the ethnographic data. Responses revealed a connection between human and animal welfare. Workers saw human welfare as a prerequisite to animal welfare, and cattle welfare as potentially mutually beneficial to humans. Some workers also saw an ethical obligation towards providing cattle with good welfare. Though some workers were unfamiliar with the term ‘animal welfare’, in daily practice caring for cattle led farm workers to ponder, prioritize, and make decisions relevant to welfare including lameness, morbidity, and nutrition. Workers in management positions appeared to embrace evidence-based animal care improvements, especially those which were perceived to also benefit people. Based on our findings, we suggest animal welfare initiatives should 1) consider worker welfare, 2) clearly communicate the concept of ‘animal welfare’, 3) identify mutual benefits, and 4) provide pragmatic, evidence-based strategies to improve welfare.